Pioneer Farmer Manual: Step-by-step guide on How to use citizen science data collection form - Njamba, Harrison; Kiptoo, Emmaculate; Gichuki, Leah; Maiyo, Nathan (International Livestock Research Institute, 2024)
The citizen science data collection guide is designed to help pioneer farmers collect and submit farm records on dairy production to the scientist at ILRI. The manual focuses on information for data collectors[farmers] to keep monthly farm records and make observations on changes happening on the farm. The guide will assist pioneer farmers in filling out the Livestock and Climate Initiative data collection questionnaire. Pioneer households are expected to fill out the ODK form at the end of every month and send it to the research team by the 2nd day of the following month. The answers the farmer enters on this form are largely informed by the recording-keeping sheets that they fill regularly.